Rural development: Lessons never learnt - Shadreck Tanyanyiwa (Academic Journals (A J), 2023)
Life is supposed to be a great teacher, but in the development field lessons have never been learnt because errors of decades ago continue being entrenched today, by more enlightened peopleThis paper deploys critic theories of rural development and community participation to explain why communities resist development projects. One such incident is community resistance to a donor-funded mega irrigation project in Nyangavi, Guruve, in Northern Zimbabwe. The community felt that the poverty alleviation project was imposed on them. The resilient modernisation’ thinking countered by people-centred ideas of development in Guruve promotes active participation of rural communities as subjects rather than objects of development. Resistance in this paper is underscored to highlight the lack of fit between rural development policy and the actual implementation on the ground and underscores rural communities’ agency as masters of their own destiny.National governments have explicit rural development policies that can help rural communities drive economies. However, these policies are ignored, for expedience purposes as officials futilely fast-track change that is meant to improve the standard of living of the poor. There appears to be selective use of community participation policies to suit certain conditions.This kind of development characterises most of Africa and development of billion-dollar projects throughout the world.